Antireflective and self-cleaning glass with robust moth-eye surface nanostructures for photovoltaic utilization. (January 2019) - Luo, Xiaolei; Lu, Linfeng; Yin, Min; Fang, Xiaohong; Chen, Xiaoyuan; Li, Dongdong; Yang, Liyou; Li, Gaofei; Ma, Jing
Graphical abstract: Mechanical robust moth-eye glass were prepared through inductively coupled plasma (ICP) etching using thermal dewetted copper (Cu) nanoparticles masks. The excellent omnidirectional and broadband antireflection ability greatly enhances the performance of photovoltaic (PV) modules especially at higher incidence angels. The additional superhydrophilic self-cleaning and anti-fogging properties can help solving the dust accumulation and fogging condensation problems of PV modules outdoor. Highlights: Biomimetic moth-eye glass was realized via dry etching using nanoparticles masks. Chemically strengthening ensured the mechanical durability of moth-eye glass. The moth-eye glass shows omnidirectional and broadband antireflection ability. The relative PCE improved from 4.6% to 9.9% at incident angle of 0° and 60°. The moth-eye glass shows superhydrophilic self-cleaning and anti-fogging abilities. Abstract: Omnidirectional and broadband antireflection (AR) self-cleaning coatings are crucial for the performance enhancement of photovoltaic (PV) modules. Herein, we demonstrate biomimetic moth-eye structures on glass through inductively coupled plasma (ICP) etching process using thermal dewetted copper nanoparticles as the masks. Moreover, the etched glasses are chemically treated to strengthen the nanostructures. The moth-eye glass exhibits excellent AR effects with a reflectance below 3% over the wavelength range from 570 to 950 nm. As the incident angles of the light increasing from 0o to 60o, the relative improvement of the power conversion efficiency (PCE) of PV module with moth-eye glass produces a dramatically increases from 4.6% to 9.9%, compared with that of PV modules with flat glass. Additionally, the moth-eye glass also possesses superhydrophilic self-cleaning and antifogging abilities, which are attractive for outdoor applications.